Schwannoma neck: a diagnostic dilemma - Manohar, Babu; Abdurahiman, Raees (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Schwannomas are less common benign slow growing tumors originating from Schwann cells. In the head and neck region, schwannomas arise most commonly from the vagus nerve or the sympathetic chain. We present this case as the location of schwannoma is extremely rare and due to the diagnostic difficulties it posed. A 48 year old male presented with right neck swelling and breathing difficulty to our OPD. Patient underwent ultrasonogram of neck, MRI neck and Fine needle aspiration cytology (FNAC) of the lesion. Each of the investigations suggested different pathology which made the diagnosis challenging. During surgery, the lesion was found to arise from right recurrent laryngeal nerve. After excision of the lesion, the patient developed hoarse voice and the pathological examination revealed schwannoma. Schwannomas that originate from Schwann cells can affect any part of the body. MRI, CT, USG and FNAC have been suggested in the literature for diagnosing the lesion. Trucut biopsy should be considered in situations where FNAC becomes inconclusive. Surgical excision is the treatment of choice. Histologically, five variants of schwannomas have been described in the literature namely common, plexiform, cellular, epithelioid and ancient schwannoma. To conclude, schwannoma arising from RLN which masqueraded as a thyroid swelling is a rare entity. The diagnostic modalities suggested in the literature were unable to pin point the diagnosis. Once, FNAC shows an inadequate specimen, a trucut biopsy should be considered as the next investigation modality.